The Interrelatedness of Adverse Childhood Experiences Among High-Risk Juvenile Offenders. (July 2016) - Baglivio, Michael T.; Epps, Nathan
The interrelatedness of adverse childhood experiences (ACEs) in 64, 329 juvenile offenders was examined. ACEs include childhood abuse (physical, emotional, and sexual), neglect (physical and emotional), and household dysfunction (family violence, family substance use, family mental illness, separation/divorce, and family incarceration). Prevalence ranged from 12% to 82% for each ACE. Of youth experiencing one ACE 67.5% reported four or more additional exposures and 24.5% exposure to six or more additional ACEs. Females have higher prevalence and multiple exposures. ACEs are interrelated, necessitating assessment of multiple ACEs rather than one or a few. ACE exposure differs by gender and race/ethnicity.